2011
DOI: 10.3851/imp1897
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Lipid Abnormalities among Antiretroviral-Naive HIV-Infected Asian Children with Mild-To-Moderate Immunosuppression

Abstract: Background Dyslipidemia is a common complication among HIV-infected children after antiretroviral therapy (ART). However, HIV itself can cause abnormal lipid metabolism. There is limited information of lipid profile among Asian HIV-infected children naïve to ART. Methods 274 HIV-infected ART-naïve Thai and Cambodian children 1–12 years of age with CD4 between 15–24% were included. Patients were fasted for ≥ 4 hours before blood was drawn. Abnormal lipid level was defined as triglyceride (TG) > 130 mg/dL, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 21 publications
5
27
0
1
Order By: Relevance
“…This may be explained by the fact that most studies have been done in adults and also populations different from ours. Also other factors that affect HDL include genetics and environmental factors like alcohol consumption [9,12,13]. These differences in the previous study populations may explain the difference in the prevalence of HDL seen in this study population.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This may be explained by the fact that most studies have been done in adults and also populations different from ours. Also other factors that affect HDL include genetics and environmental factors like alcohol consumption [9,12,13]. These differences in the previous study populations may explain the difference in the prevalence of HDL seen in this study population.…”
Section: Discussionmentioning
confidence: 96%
“…It was important to consider HDL in the study because HDL has been shown to be cardio-protective [11]. Studies that included all the 4 lipids have found a relatively high prevalence [9]. There are not many studies explaining low HDL among children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ainsi, une étude menée chez les PV-VIH naïfs d'ARV a rapporté une fréquence élevée de dyslipidémies avec hypo HDLcholestérolémie et hypertriglycéridémie. Ces auteurs ont aussi trouvé que l'intensité de ces troubles était en rapport avec le niveau de la charge virale plasmatique ARN VIH (Kanjanavanit et al, 2011). La nature des mutations et/ou leur nombre pourraient être à l'origine des troubles lipidiques observés chez les PV-VIH et expliqueraient la variabilité de l'intensité de ces troubles d'un sujet à l'autre.…”
Section: Discussionunclassified